Hubungan Antara Pengetahuan Tentang Ekosistem, Locus of Control dan Kecerdasan Naturalis dengan Pro Environmental Behavior Masyarakat Grogol Petamburan - Ramdani, Denny (IJEEM - Indonesian Journal of Environmental Education and Management, 2018)
The objective of this research is to know: 1) the relationship between Ecosystem Knowledge with Pro Environmental Behavior of Grogol Petamburan Community, 2) the relationship between Locus of Control with Pro Environmental Behavior of Grogol Petamburan Community, 3) the relationship between Naturalisttic Intelegence with Pro Environmental Behavior of Grogol Petamburan Community and 4) the relationship between Ecosystem Knowledge, Locus of Control and Natulalisttic Intelegece with Pro Environmental Behavior of Grogol Petamburan Community. The research was conducted at Grogol Petamburan regencies of Jakarta province with 90 of respondets. Sample was taken by multi stageS random sampling technique. The result of the study showed that: (1) there was a positive correlation between Ecosystem Knowledge with Pro Environmental Behavior of Grogol Petamburan Community, (2) there was a positive correlation Locus of Control with Pro Environmental Behavior of Grogol Petamburan Community, (3) there was a positive correlationship between Naturalisttic Intelegence with Pro Environmental Behavior of Grogol Petamburan Community, and (4) there was a positive correlation between Ecosystem Knowledge, Locus of Control and Natulalisttic Intelegence with Pro Environmental Behavior of Grogol Petamburan Community.It can be concluded that Ecosystem Knowledge, Locus of Control and Naturalisttic Intelegence can increase the Pro Environmental Behavior of Community.